2016
DOI: 10.1002/etc.3432
|View full text |Cite
|
Sign up to set email alerts
|

From macroplastic to microplastic: Degradation of high‐density polyethylene, polypropylene, and polystyrene in a salt marsh habitat

Abstract: As part of the degradation process, it is believed that most plastic debris becomes brittle over time, fragmenting into progressively smaller particles. The smallest of these particles, known as microplastics, have been receiving increased attention because of the hazards they present to wildlife. To understand the process of plastic degradation in an intertidal salt marsh habitat, strips (15.2 cm × 2.5 cm) of high-density polyethylene, polypropylene, and extruded polystyrene were field-deployed in June 2014 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
191
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 444 publications
(201 citation statements)
references
References 33 publications
3
191
1
6
Order By: Relevance
“…Recently, it has also been shown that microplastic fragments and fibers were produced from high density polyethylene, polypropylene, and polystyrene strips after 8 weeks of exposure in an intertidal salt marsh (Weinstein et al 2016).…”
Section: Abundance Of Microplastics In the Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has also been shown that microplastic fragments and fibers were produced from high density polyethylene, polypropylene, and polystyrene strips after 8 weeks of exposure in an intertidal salt marsh (Weinstein et al 2016).…”
Section: Abundance Of Microplastics In the Environmentmentioning
confidence: 99%
“…Microplastics (MPs) have been generally defined as plastic particles that have at least 1 dimension less than 5 mm (Andrady 2011) and can be further classified by the origin of the microplastics. Primary microplastics are intentionally manufactured to have micron-sized dimensions, whereas secondary microplastics have fragmented from a larger plastic product, eventually reaching micron-sized dimensions (Weinstein et al 2016). The presence of microplastics in the environment has been widely addressed and confirmed in both aquatic and terrestrial ecosystems (Browne et al 2011;Rillig 2012).…”
Section: Introductionmentioning
confidence: 99%
“…When discarded macroplastics are exposed to the elements, microfragments can be generated in situ as a result of ultraviolet, thermal, and oxidative weathering. These processes cause embrittlement, which promotes fracturing (Weinstein et al 2016); embrittled plastics become more susceptible to physical abrasion and mechanical fragmentation (Andrady, 2011). The dispersion of these plastic particles in the environment has been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…To prevent this, additives are added during the production process, and the oxidative or photooxidative degradation of the polymer is delayed until the antioxidants are consumed. After the initial oxidation of the surface of polyolefins, the degradation could occur in several weeks but results in the formation of microplastics as possible intermediates [67]. These smaller and oxidized plastic fragments are more susceptible to microbial attack, e.g., biodegradation of PE is described for pre-oxidized fragments of the original material by Pseudomonas sp.…”
Section: Environmental Degradation Of Synthetic Polymersmentioning
confidence: 99%